2017
DOI: 10.3389/fpls.2017.00851
|View full text |Cite
|
Sign up to set email alerts
|

Grape Composition under Abiotic Constrains: Water Stress and Salinity

Abstract: Water stress and increasing soil salt concentration represent the most common abiotic constrains that exert a negative impact on Mediterranean vineyards performance. However, several studies have proven that deficit irrigation strategies are able to improve grape composition. In contrast, irrigation with saline waters negatively affected yield and grape composition, although the magnitude of these effects depended on the cultivar, rootstock, phenological stage when water was applied, as well as on the salt con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 77 publications
3
57
0
1
Order By: Relevance
“…In semi-arid areas exposed to water scarcity, re-using wastewater is an attractive practice to promote water and cost savings. However, water quality, mainly in regards of a too high salt concentration, inducing salt stress, can have detrimental effects on overall vineyard performance (Costa et al, 2016;Laurenson et al, 2012), more specifically on vine transpiration (Pereira et al, 2015) and can negatively affect yield and berry composition and consequently final wine quality (Miras-Avalos and Intrigliolo, 2017). Using moderately saline water for deficit irrigation, Degaris et al (2016) reported an effect on ion partitioning (Cl -, Na + , and K + ) in grapevines berries.…”
Section: Towards a Site-specific Deficit Irrigation Strategy?mentioning
confidence: 99%
“…In semi-arid areas exposed to water scarcity, re-using wastewater is an attractive practice to promote water and cost savings. However, water quality, mainly in regards of a too high salt concentration, inducing salt stress, can have detrimental effects on overall vineyard performance (Costa et al, 2016;Laurenson et al, 2012), more specifically on vine transpiration (Pereira et al, 2015) and can negatively affect yield and berry composition and consequently final wine quality (Miras-Avalos and Intrigliolo, 2017). Using moderately saline water for deficit irrigation, Degaris et al (2016) reported an effect on ion partitioning (Cl -, Na + , and K + ) in grapevines berries.…”
Section: Towards a Site-specific Deficit Irrigation Strategy?mentioning
confidence: 99%
“…Finally, Herrera et al [114] suggest that the interaction between water availability and weather conditions plays a crucial role in modulating berry composition. A meta-analysis performed by Mirás-Avalos and Intrigliolo [115], using published data for red and white varieties, concludes that cultivar, the timing of water restrictions and rootstock type have a great influence on must and wine composition. The The effect of RDI on grape volatile and phenolic compounds remains incompletely understood, and further investigations are required to determine what compounds are influenced by irrigation.…”
Section: Effects Of Vine Irrigation On Berry Phenolic Maturity and Armentioning
confidence: 99%
“…On other hand, deficits occurring during the maturation of fruits show positive impacts on soluble sugar accumulation and enhancement of fruit aroma. The level of stress that benefits the entire cycle of the plant is likely to be depend, simultaneously, on species and environmental conditions, but when a certain threshold of water stress is surpassed, the beneficial effects are no longer observed [23,24].…”
Section: Abiotic Stresses: Temperature and Water Availabilitymentioning
confidence: 99%